Female Representation: Australian Diabetes and Endocrinology Societies - Raven, Lisa M.; McCormack, Ann I. (Frontiers in Endocrinology, 2022)
Background: Endocrinology has one of the highest proportions of female specialists and trainees, however females have traditionally been underrepresented in leadership positions and as speakers at scientific meetings. Hypothesis: Females would represent less than half of invited speakers (plenary, symposium sessions) at endocrinology conferences and in leadership positions of endocrinology societies. Method: An audit of Australian diabetes and endocrinology societies and their respective annual scientific meetings between 2016 – 2020. Analysis of the gender of conference speakers across oral, symposium and plenary sessions, session chairs, program organising committees and society committees. Results: A total of 1638 speakers (females 856, 52.3%) across 550.4 hours (females 273.6, 49.7%) of presentations at the conferences were identified. Among plenary sessions of all 3 societies there were more male (61%) than female speakers. A total of 608 session chairs were identified, with 313 (51.5%) females. The majority of organising committee members (n=116) were female (56%), however the representation across each organising committee varied. There was a low proportion of society female council members (39% female). Conclusion: There was an equal representation of females and males as conference speakers and session chairs. However, there was an underrepresentation of women in more prestigious roles of plenary speakers and society council members. We implore conscious efforts to address this disparity.